Effect of severe acute respiratory syndrome coronavirus 2 antibodies on outcomes of dengue infected children: A retrospective observational study - Sravani Kolla; Lokeswari Balleda; Chandra Sekhara Reddy Thimmapuram (Wolters Kluwer Medknow Publications, 2022)
Background: Dengue virus and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) share similar antigenic properties. In some studies, it has been shown that immunological memory/antibodies to dengue virus in endemic countries reduces the severity and spread of COVID-19. It is not known whether SARS-CoV-2 antibodies reduce or augment the severity of dengue viral infections. This study aims to evaluate the effects of SARS-CoV-2 antibodies on the outcomes of dengue infection in children. Subjects and Methods: This was a retrospective observational study conducted at the pediatric emergency and intensive care units and wards of a tertiary care teaching hospital in Andhra Pradesh, India, between August and November 2021. Results: About 400 children with dengue infection were admitted to our hospital, of which 96 children also had SARS-CoV-2 antibody titers estimated. In 50 (52.08%) of these 96 children, SARS-CoV-2 antibodies (IgG and/or IgM) were positive. In these 96 children, clinical severity and outcomes of dengue infection were compared between the two groups, i.e., with and without SARS-CoV-2 antibody positivity. Conclusions: The present study provides preliminary evidence that outcome and severity of dengue infection in children are not affected by the SARS-CoV-2 antibody positivity.